2022
DOI: 10.3389/fnut.2022.1008514
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in ischemic stroke: Where we stand and challenges ahead

Abstract: Gut microbiota is increasingly recognized to affect host health and disease, including ischemic stroke (IS). Here, we systematically review the current understanding linking gut microbiota as well as the associated metabolites to the pathogenesis of IS (e.g., oxidative stress, apoptosis, and neuroinflammation). Of relevance, we highlight that the implications of gut microbiota-dependent intervention could be harnessed in orchestrating IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 180 publications
0
4
0
Order By: Relevance
“… 42 Multiple mechanisms linking microbiota as well as the associated metabolites have been proposed to play a role in pathogenesis of ischemic stroke, including oxidative stress, apoptosis, and neuroinflammation. 43 The current study examined the role of the microbiome in the regulation of neuroinflammation, but the other factor affecting infant brain susceptibility to hypoxia-ischemia due to gut-brain interaction remains to be discovered. Infant microbiota is increasingly recognized as a critical contributor to brain cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Multiple mechanisms linking microbiota as well as the associated metabolites have been proposed to play a role in pathogenesis of ischemic stroke, including oxidative stress, apoptosis, and neuroinflammation. 43 The current study examined the role of the microbiome in the regulation of neuroinflammation, but the other factor affecting infant brain susceptibility to hypoxia-ischemia due to gut-brain interaction remains to be discovered. Infant microbiota is increasingly recognized as a critical contributor to brain cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GM plays a crucial role in the synthesis and release of various hormones, neurotransmitters, and active metabolites, which orchestrate host metabolism and immune function, consequently influencing brain function and host behavior. 20 For instance, certain microbial genera such as Faecalibacterium , Oscillibacter , Roseburia , Bifidobacterium , Coprococcus , and Butyrivibrio contribute to immunomodulation through the production of SCFAs and bile acids, exerting a protective effect on the ischemic brain. 9,21,22 Conversely, genera like Prevotella , Klebsiella , and Fusobacterium have been associated with heightened inflammation and exacerbated neural damage.…”
Section: Discussionmentioning
confidence: 99%
“…Over 50% of patients with IS experience gastrointestinal complications, including swallowing difficulties, intestinal motility and absorption disorders, gastrointestinal bleeding, intestinal leakage, fecal incontinence, and intestinal septicemia (Durgan et al, 2019;Long et al, 2022). Extensive research in genomics, metabolomics, and proteomics has revealed that the gut microbiota is involved in several pathophysiological events following stroke, and patients with IS with gastrointestinal complications often have a poor prognosis, high mortality rate, and neurological function deterioration (Tuz et al, 2022;Zhao et al, 2023).…”
Section: Gut Microbiota and Post-is Gastrointestinal Dysfunctionmentioning
confidence: 99%